A self-directed digital exercise program for hip osteoarthritis (“My Hip Exercise”): protocol for a randomised controlled trial - Kim L. Bennell; Rachel K. Nelligan; Michelle Hall; Sarah Stratulate; Fiona McManus; Karen Lamb; Jennifer Marlow; Rana S. Hinman (BMC Musculoskeletal Disorders, 2023)
Abstract Background Hip osteoarthritis (OA) is a leading global cause of chronic pain and disability. Given there is no cure for OA, patient self management is vital with education and exercise being core recommended treatments. However, there is under-utilisation of these treatments due to a range of clinician and patient factors. Innovative service models that increase patient accessibility to such treatments and provide support to engage are needed. This study primarily aims to determine the effects of a self-directed digital exercise intervention comprising online education and exercise supported by a mobile app to facilitate adherence on the primary outcomes of changes in hip pain during walking and patient-reported physical function at 24-weeks when compared to online education control for people with hip OA. Methods We will conduct a two-arm, superiority parallel-design, randomised controlled trial involving 182 community volunteers aged 45 years and over, with painful hip OA. After completing the baseline assessment, participants will be randomly assigned to either: i) digital exercise intervention; or ii) digital education (control). Participants randomised to the intervention group will have access to a website that provides information about hip OA and its management, advice about increasing their physical activity levels, a 24-week lower limb strength exercise program to be undertaken at home three times per week, and a mobile app to reinforce home exercise program adherence. Participants in the control group will have access to a website containing only information about hip OA and its management. All participants will be reassessed at 24 weeks after randomisation. Primary outcomes are severity of hip pain while walking using an 11-point numeric rating scale and physical function using the Western Ontario and McMaster Universities Osteoarthritis Index subscale. Secondary outcomes are the Hip dysfunction and Osteoarthritis Outcome Score subscales of pain, hip-related quality of life, and function, sports and recreational activities; global change in hip condition; health-related quality of life; measures of physical activity levels; fear of movement; self efficacy for pain and for exercise; and use of oral pain medications. Discussion Innovative and scalable approaches to OA education, physical activity, and exercise are required in order to improve exercise participation/engagement and mitigate physical inactivity in the hip OA population. This will help minimise the burden of this major public health issue on individuals and society. Trial registration Australia New Zealand Clinical Trials Registry (ACTRN12622001533785).